An insider action research on improving the recovery rate of the AIFMD reporting service of a fund administration firm - Rosales, Zyrine Joy O. (Animo Repository, 2020)
This action research addressed the improvement of the recovery rate of the AIFMD Reporting Service (the "Service"), one of the ancillary services of A Philippines Inc. The increase in the recovery rate means a reduction in excessive time charges. The low recovery rate of the Service has a two-fold effect. Firstly, it wasn't able to generate the desired profit. Secondly, excessive time charges mean that employees are working longer than expected, which resulted in unwanted overtime to finish the work and meet the deadline, which may contribute to the dissatisfaction of the employees. Alongside my collaborators, we have identified the issue and its root cause using the Why's Framework and other action research tools. We collaboratively planned and implemented the interventions needed to improve the situation. Our goal is to meet the 100% recovery rate. We've gone through two cycles to improve the current situation. During the first cycle, we managed to improve the staff allocation planning, which contributed to a better recovery rate. After evaluation of our Cycle 1, we've agreed that we need to equip the employees to do the role thoroughly. Hence, we designed a more intensive training program. Q4 2019 reporting resulted in an 80% recovery rate (2018: 65%). Even if we did not meet the 100% recovery rate, due to several factors, the collaborators and I were happy to see that we've reached this far. The team and I will continue to exert efforts to improve the recovery rate of the Service.